Financial Performance Analysis Of Pt. Smartfren Telecom Tbk Using The Profitability And Solvability Ratio Approach From 2020 To 2024 - Annisa Nur Ramadhani; Aulia Pasaribu; Dini Syarafina; Finanty Yolanda; M. Rafi Akbar Dirja; Priskila Tafonao; Yohana Pangaribuan; Anggi Pratama Nasution (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the financial performance of PT Smartfren Telecom Tbk during the period 2020–2024. The analysis is conducted using two approaches, namely profitability ratios and solvency ratios. The profitability ratios examined include Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE). Meanwhile, the solvency ratios analyzed are the Debt to Asset Ratio (DAR) and the Debt to Equity Ratio (DER). This research employs a descriptive quantitative method, using secondary data obtained from the annual financial statements published by the Indonesia Stock Exchange (IDX). The results of the study indicate that the company’s profitability performance, as measured by NPM, ROA, and ROE, consistently falls into the Very Poor category. This condition is influenced by the impact of the COVID-19 pandemic and high operating expenses, although the company recorded a profit in 2022. In contrast to profitability, the solvency ratios, namely DAR and DER, show a significant improving trend, particularly in 2024, when the company successfully reduced its debt and strengthened its capital structure.